Perforant Path Fiber Loss Results in Mnemonic Discrimination Task Deficits in Young Rats - Burke, Sara N.; Turner, Sean M.; Desrosiers, Courtney L.; Johnson, Sarah A.; Maurer, Andrew P. (Frontiers in Systems Neuroscience, 2018)
The observation that entorhinal input to the hippocampus declines in old age is well established across human studies and in animal models. This loss of perforant path fibers is exaggerated in individuals with episodic memory deficits and Mild Cognitive Impairment, suggesting that perforant path integrity is associated with progression to Alzheimer’s Disease. During normal aging, behaviors that measure the ability of a study participant to discriminate between stimuli that share features is particularly sensitive to perforant fiber loss. Evidence linking perforant path changes to cognitive decline, however, has been largely correlational. Thus, the current study tested the causative role of perforant path fiber loss in behavioral decline by performing a unilateral knife cut to disconnect the entorhinal cortex from the hippocampus in the right hemisphere in young male and female rats. This approach does not completely disconnect the hippocampus from the entorhinal cortex but rather reduces the effective connectivity in a manner that has been suggested to be comparable to aging. Male and female rats were then tested on the rodent variant of the mnemonic discrimination task, which is believed to critically rely on perforant path fiber integrity. Right hemisphere perforant path transections produced a significant impairment in the abilities of lesioned animals to discriminate between objects with high levels of feature overlap. This deficit was not observed in the male and female sham groups that received a cut to cortex above the white matter. Together these data support the view that, across species, age-related perforant path fiber loss produces behavioral deficits in the ability to discriminate between stimuli with perceptual overlap.